The effect of soybean formula and formula 100 supplementation on the growth of preschool children - M Mexitalia; Yohanes Tri Nugroho; J C Susanto (Indonesian Pediatric Society, 2005)
Background Preschool children are vulnerable in growth. Soy-bean formula (SF) and formula-100 (F100) are supplementary foodswhich contain of high energy and are available at low price; how-ever, they are not widely used for preschool children.Objectives To investigate the effect of SF compared to F100 onthe growth of preschool children.Methods A cross-over trial was conducted on 96 preschool chil-dren aged 4-7 years. Subjects were randomly divided into 2 groupswhich received 200 ml soybean formula (n=49) or F100 (n=47) for1 month and crossed-over after a six-week wash-out period. Bodyweight was measured weekly. Body height and food analysis by 3-day food recall were measured at the beginning and the end of thestudy. The criteria of the acceptability of the formula was eithergood or poor.Results Supplementation with SF as well as F100 induced catchup growth as shown by the increase of Î”z-score. There were nosignificant difference of Î” weight for age z-score, Î” height for agez-score, and Î” weight for height z score between groups duringthe first and second phases of the trial. The acceptability of F100was significantly better than that of SF at the beginning; neverthe-less, the difference was not significant at the second phase trial.Conclusions Soybean formula and F100 given for a one monthperiod can induce catch-up growth in preschool children. Soybeanformula as an alternative health food can be accepted by preschoolchildren